Structural variation in organically templated uranium sulfate fluorides. - Doran, M; Cockbain, B; O'Hare, D (2005)
The ability of templated uranium sulfate fluorides to adopt diverse inorganic architectures is demonstrated in six novel materials. The inorganic structures present in [N2C6H16][UO2F2(SO4)](USFO-2), [N2C6H16][UO2F(SO4)]2(USFO-3), [N2C3H12][UO2F(SO4)]2.H2O (USFO-4), [N2C5H14][UO2F(H2O)(SO4]2(USFO-5), [N2C6H18]2[UO2F(SO4)]4.H2O (USFO-6) and [N2C3H12][UO2F(SO4)]2.H2O (USFO-7) range from infinite chains to five different layer topologies. The chain, and two of the five layers, have unprecedented structure types. These compounds illustrate the structural diversity within this new family of materials, arising from the varied coordination of the U6+ centres. Each material was synthesised under hydrothermal conditions, through reaction of uranyl acetate, sulfuric acid, HF(aq), water, and the respective organic template.